Ecological studies of two abundant macroalgae on a Caribbean coral reef. - Van Steveninck, Erik Douwe De Ruyter (Groningen Netherlands Drukkeij van Denderen B.V., 1987)
Dissertation to acquisition of the doctorate in Mathematics and Natural Sciences at the state University to Groningen on authority of the Rector of Magnificus Dr. E. Bleumink openly to defend on Friday 19 June 1987 of the afternoons to 2.45 hour precisely through
Keywords: Microalgae